Regional Cultural Diversity, Government Intervention and M&A Performance: Based on the Cultural Differences - Jianquan Guo; Hongdi Wang (International Journal of Empirical Economics, 2023)
Based on a sample of cross-border mergers and acquisitions (M&A) by Chinese enterprises in different target countries between 2010 and 2020, this paper explores the impact of cultural differences on M&A performance and the moderating effects of regional cultural diversity and government intervention (financial subsidies) by using event study method and regression analysis. The results indicate that cultural differences have a negative impact on M&A performance. Furthermore, regional cultural diversity and government intervention positively moderate the relationship between cultural differences and M&A performance. This research can assist Chinese companies in fully leveraging regional cultural diversity to mitigate cultural differences and enhance their corporate performance.